Assay of Some Thromboplastin Generation Factors - Colman, R; Alexander, B (Thrombosis and Haemostasis, 1965)
A method for measuring six plasma or serum factors required for intrinsic thromboplastin formation is described by which various dilutions of normal serum are used to correct the abnormal TGT obtained with specifically deficient blood. When the arithmetic product of the minimum clotting time and the corresponding incubation time are plotted against the logarithm of the concentration of the particular factor in question, a rectilinear relationship is obtained for factors V, VIII, IX, XI and XII, and a hitherto unrecognized new serum factor (Thorium Vulnerable Factor, TVF). This correlation does not hold for factor X. Thus far no mathematical or biochemical equation could be formulated to explain the empiric observations.Other reported assay procedures are discussed.